Pengaruh Ketidakpastian Lingkungan Dan Desentralisasi Terhadap Hubungan Antara Karakteristik Sistem Akuntansi Manajemen Dengan Kinerja Manajerial(Studi kasus pada PT Kebayoran Pharma) - Prastiyo, Febri Tri; , Dr. Fatchan Achyani, M.Si (2016)
This study aims to to scrutinize influence characteristic of accounting system management ( sam of performance managerial in ptkebayoranpharma , variable decentralization and uncertainty environment as variable moderating .Of data consists of 40 respondents were uses the method purposive sampling .The result of this research shows that characteristic of accounting system management have had a positive impact on performance managerial , decentralization impact on performance managerial and uncertainty environmental impact on performance managerial .The relationship between characteristic of accounting system management ( sam and decentralization impact on performance managerial .While the relationship between characteristic of accounting system management ( sam ) and uncertainty environmental impact on performance managerial .